2021
DOI: 10.3390/ijms222413198
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of p53 Tumour Suppressor Posttranslational Modifications and TTC5 Cofactor in Lung Cancer

Abstract: Mutations in the p53 tumor suppressor are found in over 50% of cancers. p53 function is controlled through posttranslational modifications and cofactor interactions. In this study, we investigated the posttranslationally modified p53, including p53 acetylated at lysine 382 (K382), p53 phosphorylated at serine 46 (S46), and the p53 cofactor TTC5/STRAP (Tetratricopeptide repeat domain 5/ Stress-responsive activator of p300-TTC5) proteins in lung cancer. Immunohistochemical (IHC) analysis of lung cancer tissues f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…HIF1 overexpression, oncogene activation (cMyc, K-ras- mTORC1, and Akt), activation of signaling pathways (PI3K/Akt/mTORC1, Ras/Raf/MEK/ERK), an increase in glucose (GLUT) and lactate (MCT4) transporters, and the activation of glycolytic enzymes (HK2, PFK1, ENO1, PKM2, and LDHA) ( Wallace, 2005 ; Choudhury et al, 2020 ; Han et al, 2021 ; Mariani et al, 2021 ; Pluimakers et al, 2021 ; Shen et al, 2021 ; Vaupel and Multhoff, 2021 ; Zhu et al, 2022c ) are all part of the metabolic change observed in cancer cells. Furthermore, the functions of tumor suppressors (mutant p53, mutant PTEN, and microRNAs 29, 143, and 144), Sirtuins 3 and 6, and the AMPK signaling pathway ( Kumar et al, 2016 ; Alhebshi et al, 2021 ; Jazvinšćak Jembrek et al, 2021 ; Zhang et al, 2022a ) are inhibited to prevent cell death and reduce metabolic stress of tumor cells. The metabolic changes belonging to the Warburg effect can be influenced by the known physiological hormetic triggers that could serve as primary and perhaps secondary preventive interventions ( Jazvinšćak Jembrek et al, 2021 ).…”
Section: Part Ii: Mitochondrial Dysfunction and Its Involvement In Di...mentioning
confidence: 99%
“…HIF1 overexpression, oncogene activation (cMyc, K-ras- mTORC1, and Akt), activation of signaling pathways (PI3K/Akt/mTORC1, Ras/Raf/MEK/ERK), an increase in glucose (GLUT) and lactate (MCT4) transporters, and the activation of glycolytic enzymes (HK2, PFK1, ENO1, PKM2, and LDHA) ( Wallace, 2005 ; Choudhury et al, 2020 ; Han et al, 2021 ; Mariani et al, 2021 ; Pluimakers et al, 2021 ; Shen et al, 2021 ; Vaupel and Multhoff, 2021 ; Zhu et al, 2022c ) are all part of the metabolic change observed in cancer cells. Furthermore, the functions of tumor suppressors (mutant p53, mutant PTEN, and microRNAs 29, 143, and 144), Sirtuins 3 and 6, and the AMPK signaling pathway ( Kumar et al, 2016 ; Alhebshi et al, 2021 ; Jazvinšćak Jembrek et al, 2021 ; Zhang et al, 2022a ) are inhibited to prevent cell death and reduce metabolic stress of tumor cells. The metabolic changes belonging to the Warburg effect can be influenced by the known physiological hormetic triggers that could serve as primary and perhaps secondary preventive interventions ( Jazvinšćak Jembrek et al, 2021 ).…”
Section: Part Ii: Mitochondrial Dysfunction and Its Involvement In Di...mentioning
confidence: 99%
“…Malignant melanoma and HCC patients with high levels of p53 Lys373 acetylation have relatively longer OS and early, lower lymph node metastasis 98,99 . HCC, malignant melanoma, and lung cancer patients with high levels of p53 Lys382 acetylation have relatively longer OS and earlier stage and lower lymph node metastasis 98–100 …”
Section: The Structure Mutation and Modification Of P53mentioning
confidence: 99%
“… 98 , 99 HCC, malignant melanoma, and lung cancer patients with high levels of p53 Lys382 acetylation have relatively longer OS and earlier stage and lower lymph node metastasis. 98 , 99 , 100 …”
Section: The Structure Mutation and Modification Of P53mentioning
confidence: 99%